Demographic transition, demographic dividend and economic growth in Nigeria (2012)
Changes in age structure that results from demographic transition have economic consequences. This paper identifies the period of potential window of opportunity or demographic dividends created by Nigeria’s demographic transition. This is done by simulating the period of the demographic window of opportunity in Nigeria. In a simulation covering 1950 – 2050 our results reveal that Nigeria entered the window of opportunity in 2003 and will last beyond year 2050. The highest benefit will accrue in years 2032 and 2033 when the dividend can account for more than 10% of the growth of GDP per capita even if the current performance scenario continues to exist. However, the paper notes that the demographic dividend is not automatically realized and Nigeria needs to embark on strategies that will develop her human capital and position her towards not only capturing the first dividend but the second dividend as well.